Accounting for activity respiration results in realistic trophic transfer efficiencies in allometric trophic network (ATN) models - Nadja J. Kath; Alice Boit; Christian Guill; Ursula Gaedke (Theoretical Ecology, 2018)

Climate change impacts in Latin America and the Caribbean and their implications for development - Christopher P.O. Reyer; Sophie Adams; Torsten Albrecht; Florent Baarsch; Alice Boit; Nella Canales Trujillo; Matti Cartsburg; Dim Coumou; Alexander Eden; Erick Fernandes; Fanny Langerwisch; Rachel Marcus; et al. (Regional Environmental Change, 2017)

Large‐scale impact of climate change vs. land‐use change on future biome shifts in Latin America - Alice Boit; Boris Sakschewski; Lena Boysen; Ana Cano‐Crespo; Jan Clement; Nashieli Garcia‐alaniz; Kasper Kok; Melanie Kolb; Fanny Langerwisch; Anja Rammig; René Sachse; Michiel van Eupen; et al. (Global Change Biology, 2016)
Climate change and land‐use change are two major drivers of biome shifts causing habitat and biodiversity loss. What is missing is a continental‐scale future projection of the estimated relative impacts of both drivers on biome shifts over the course of this century. Here, we provide such a projection for the biodiverse region of Latin America under four socio‐economic development scenarios. We find that across all scenarios 5–6% of the total area will undergo biome shifts that can be attributed to climate change until 2099. The relative impact of climate change on biome shifts may overtake land‐use change even under an optimistic climate scenario, if land‐use expansion is halted by the mid‐century. We suggest that constraining land‐use change and preserving the remaining natural vegetation early during this century creates opportunities to mitigate climate‐change impacts during the second half of this century. Our results may guide the evaluation of socio‐economic scenarios in terms of their potential for biome conservation under global change.

Leaf and stem economics spectra drive diversity of functional plant traits in a dynamic global vegetation model - Boris Sakschewski; Werner von Bloh; Alice Boit; Anja Rammig; Jens Kattge; Lourens Poorter; Josep Peñuelas; Kirsten Thonicke (Global Change Biology, 2015)
Functional diversity is critical for ecosystem dynamics, stability and productivity. However, dynamic global vegetation models ( DGVM s) which are increasingly used to simulate ecosystem functions under global change, condense functional diversity to plant functional types ( PFT s) with constant parameters. Here, we develop an individual‐ and trait‐based version of the DGVM LPJ mL (Lund‐Potsdam‐Jena managed Land) called LPJ mL‐ flexible individual traits ( LPJ mL‐ FIT ) with flexible individual traits) which we apply to generate plant trait maps for the Amazon basin. LPJ mL‐ FIT incorporates empirical ranges of five traits of tropical trees extracted from the TRY global plant trait database, namely specific leaf area ( SLA ), leaf longevity ( LL ), leaf nitrogen content ( N area ), the maximum carboxylation rate of Rubisco per leaf area ( ), and wood density ( WD ). To scale the individual growth performance of trees, the leaf traits are linked by trade‐offs based on the leaf economics spectrum, whereas wood density is linked to tree mortality. No preselection of growth strategies is taking place, because individuals with unique trait combinations are uniformly distributed at tree establishment. We validate the modeled trait distributions by empirical trait data and the modeled biomass by a remote sensing product along a climatic gradient. Including trait variability and trade‐offs successfully predicts natural trait distributions and achieves a more realistic representation of functional diversity at the local to regional scale. As sites of high climatic variability, the fringes of the Amazon promote trait divergence and the coexistence of multiple tree growth strategies, while lower plant trait diversity is found in the species‐rich center of the region with relatively low climatic variability. LPJ mL‐ FIT enables to test hypotheses on the effects of functional biodiversity on ecosystem functioning and to apply the DGVM to current challenges in ecosystem management from local to global scales, that is, deforestation and climate change effects.

Mechanistic theory and modelling of complex food‐web dynamics in Lake Constance - Alice Boit; Neo D. Martinez; Richard J. Williams; Ursula Gaedke (Ecology Letters, 2012)
Mechanistic understanding of consumer‐resource dynamics is critical to predicting the effects of global change on ecosystem structure, function and services. Such understanding is severely limited by mechanistic models’ inability to reproduce the dynamics of multiple populations interacting in the field. We surpass this limitation here by extending general consumer‐resource network theory to the complex dynamics of a specific ecosystem comprised by the seasonal biomass and production patterns in a pelagic food web of a large, well‐studied lake. We parameterised our allometric trophic network model of 24 guilds and 107 feeding relationships using the lake’s food web structure, initial spring biomasses and body‐masses. Adding activity respiration, the detrital loop, minimal abiotic forcing, prey resistance and several empirically observed rates substantially increased the model's fit to the observed seasonal dynamics and the size‐abundance distribution. This process illuminates a promising approach towards improving food‐web theory and dynamic models of specific habitats.

More than a meal… integrating non‐feeding interactions into food webs - Sonia Kéfi; Eric L. Berlow; Evie A. Wieters; Sergio A. Navarrete; Owen L. Petchey; Spencer A. Wood; Alice Boit; Lucas N. Joppa; Kevin D. Lafferty; Richard J. Williams; Neo D. Martinez; Bruce A. Menge; et al. (Ecology Letters, 2012)
Ecology Letters (2012) 15 : 291–300 Abstract Organisms eating each other are only one of many types of well documented and important interactions among species. Other such types include habitat modification, predator interference and facilitation. However, ecological network research has been typically limited to either pure food webs or to networks of only a few (